Analysis of News Framing on the Discourse of Sandiaga Salahudin Uno's Declaration as a Presidential Candidate for 2024 on the Detik.com Portal - Intan Permatasari (Randwick International of Social Science Journal, 2022)
The research entitled "Analysis of News Framing on the Discourse of Sandiaga Salahudin Uno's Declaration as a Presidential Candidate for 2024 on the Detik.com Portal. With the aim of seeing how the news regarding the issue of Sandiaga Uno was declared to be a presidential candidate in 2024. By observing the detik.com online portal in terms of syntax, thematics, scripts and rhetoric. The researcher's theory is Zhongdang Pan and Kosicki .'s framing analysis. Qualitative research methods based on words both written and spoken from the actions seen. The results of the study said that from news one, two and three there were declarations from various groups to nominate Sandiaga Uno as President in 2024. In detik.com reporting using an inverted pyramid where the main discussion is at the beginning of the news, the structure also uses 5W + 1H but not many sources are quoted by detik.com.